2017
DOI: 10.1109/tcomm.2017.2679708
|View full text |Cite
|
Sign up to set email alerts
|

ADMM-Based Fast Algorithm for Multi-Group Multicast Beamforming in Large-Scale Wireless Systems

Abstract: Multi-group multicast beamforming in wireless systems with large antenna arrays and massive audience is investigated in this paper. Multicast beamforming design is a well-known non-convex quadratically constrained quadratic programming (QCQP) problem. A conventional method to tackle this problem is to approximate it as a semi-definite programming problem via semi-definite relaxation, whose performance, however, deteriorates considerably as the number of per-group users goes large. A recent attempt is to apply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 32 publications
(100 reference statements)
0
107
0
Order By: Relevance
“…On the other hand, if the optimal solution of the SDP problem fails to be rank-one, additional steps such as Gaussian randomization [16] need to be applied to extract a suboptimal solution for the original problem. However, it was observed that for the high-dimensional optimization problems (e.g., the number of antennas N increases), the probability of returning a rank-one solution for the SDR approach becomes low, which yields significant performance deterioration [6], [17]. To overcome the limitations of the SDR methods, we instead propose a novel DC framework in the following section to solve problem P 1 and problem P 2 .…”
Section: Problem Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, if the optimal solution of the SDP problem fails to be rank-one, additional steps such as Gaussian randomization [16] need to be applied to extract a suboptimal solution for the original problem. However, it was observed that for the high-dimensional optimization problems (e.g., the number of antennas N increases), the probability of returning a rank-one solution for the SDR approach becomes low, which yields significant performance deterioration [6], [17]. To overcome the limitations of the SDR methods, we instead propose a novel DC framework in the following section to solve problem P 1 and problem P 2 .…”
Section: Problem Analysismentioning
confidence: 99%
“…A popular way to convexify the nonconvex QCQP problem is to reformulate it as a rank-one constrained matrix optimization problem via matrix lifting, followed by the semidefinite relaxation (SDR) technique to drop the nonconvex rank-one constraint [16]. However, it was observed that the performance of SDR approach degenerates in the scenarios with large number of antennas due to its low probability of returning rank-one solutions [2], [6], [17]. To address the limitations of the popular SDR technique, in this paper, we develop a general framework to solve the rank-one constrained matrix optimization problem via difference-of-convex (DC) programming.…”
Section: Introductionmentioning
confidence: 99%
“…In [15], the authors used a successive convex approximation (SCA) approach [16]- [18] to tackle the max-min fair multi-group multicasting problem under PAPC, where each SCA sub-problem was formulated as a second order cone program. A subsequent work [19] used an alter-native reformulation which entails solving a sequence of perantenna minimization problems within a bisection framework. Then, an ADMM algorithm is proposed for (approximately) solving these per-antenna minimization problems.…”
Section: A Prior Art and Motivationmentioning
confidence: 99%
“…A high performance, low complexity successive convex approximation (SCA) based approach is proposed for solving the joint problem. Although SCA has not been considered before for joint multicast beamforming and antenna selection, our SCA framework compared to that of [15], [19]-which studied the max-min fair multicasting without antenna selection-features the following; (i) it approximates the objective function of the problem directly without introducing any additional variables or constraints, (ii) exploits the structure inherent in each SCA subproblem by using specially tailored low-complexity firstorder methods, and (iii) guarantees convergence to a stationary point.…”
Section: B Contributionmentioning
confidence: 99%
“…In [26], a primal decomposition-based algorithm and an alternating direction method of multipliers (ADMM)-based algorithm have been proposed for the SDR version of the original problem. In [27], instead of directly dealing with the relaxed problem, the authors proposed to apply ADMM for each of the convexified SCA problems, obtaining a doule-loop scheme. In [24], an ADMM-based algorithm is proposed for a distributed solution of the problem with imperfect CSI after relaxing the original problem with S-procedure.…”
mentioning
confidence: 99%